PENGARUH LATIHAN DILL SHOTING TERHADAP AKURASI TEMBAKAN PADA ANGGOTA EKSTRAKURIKULER FUTSAL DI SMPN 5 SURDE - Irpan Abdurrahman; Manaf Darmawan; M. Galang Rahmawan; Aqil Aimar Rustandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Futsal is a sport that requires good mastery of basic techniques, especially shooting. Accurate shooting is essential because it directly affects a team's ability to score goals. However, the shooting accuracy of students participating in the futsal extracurricular program at SMPN 5 Surade was still relatively low. Therefore, an effective training method is needed to improve this skill. This study aimed to determine the effect of drill shooting training on the shooting accuracy of students participating in the futsal extracurricular program at SMPN 5 Surade. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The Sample consisted of 15 students from the futsal extracurricular program at SMPN 5 Surade. Data were collected through a shooting accuracy test administered before (pretest) and after (posttest) the implementation of the drill shooting training program. The data were analyzed using the Shapiro-Wilk normality test and the Paired Sample t-Test with the assistance of SPSS software. The results showed that the mean pretest score of 15.13 increased to 20.60 in the posttest, with an average improvement of 5.47 points. The normality test indicated that the data were normally distributed. Furthermore, the Paired Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a significant effect of drill shooting training on shooting accuracy. It can be concluded that drill shooting is an effective training method for improving the shooting accuracy of futsal players. Future studies are recommended to involve larger Samples and longer training durations to obtain more comprehensive results.